Blowing the whistle on genocide Josiah E. Dubois, Jr., and the struggle for a U.S. response to the Holocaust - Medoff, Rafael 1959- (Shofar supplements in Jewish studies, 2009)
Blowing the Whistle on Genocide tells the story of a young Treasury Department lawyer who helped alert the world about the Holocaust and force U.S. government action to rescue Jews from the Nazis." "Risking his career and ignoring threats that were made against him, Josiah E. DuBois, Jr., relentlessly investigated and then exposed the State Department's suppression of news about the Holocaust and obstruction of rescue attempts." "His report, "The Acquiescence of This Government in the Murder of the Jews," helped force President Roosevelt to belatedly establish the War Refugee Board. With DuBois as one of its leaders, the board played a key role in the rescue of more than 200,000 refugees during the final months of the war." "At every turn, DuBois was confronted by officials who tried to stop him - from the powerful Assistant Secretary of State who sabotaged rescue attempts, to the War Department official who blocked DuBois's proposal to bomb Auschwitz and worked to pardon Nazi war criminals after the war." "But DuBois persevered. He overcame the obstacles and saved lives. He was America's Schindler.